Analisis Hukum Pengadaan Tanah Untuk Kepentingan Investasi Pembangunan Rempang Eco-City - Ananda, Salsabila Qudsy; Sadino, Sadino (Bacarita Law Journal, 2024)
This study is analyzing the aspect of the land release law for the development of Rempang eco city's With a focus on investment interests. Improved land release for development purposes In Indonesia, especially for investments, often brings legal implications, which cause A conflict between affected governments and communities. The study undermines mechanism Land development in the eco-friendly city of pang and review the ways of compensatio In the liberation of land in the region. By using a qualitative approach, research It USES descriptive analysis to outline the procedural grooves, plus the analysis Qualitative to interpret compensation procedures. An in-depth interview with IC Stakeholders, including pt prospered direly graha, bp batam, and indigenous communities that Affected, as well as participative observations, provide comprehensive insights. Source triangulation Data increases reliability and validity of discovery. These studies contribute to that understanding The complexity of the law surrounding land liberation for investment and offering a foundation For further research in this field.